Student Assessment in Higher Education: Perspectives and Practices from a Practitioner Inquiry (KMC Journal, 2025)
Student assessment in higher education is the systematic process of evaluating learners’ academic performance, skills and competencies to ensure quality learning outcomes and guide instructional improvement. This study investigates how teachers at Tribhuvan University perceive student assessments, exploring their experiences with various evaluation methods in higher education. It highlights the effectiveness and challenges teachers face during these processes. Utilizing a practitioner enquiry and phenomenological design of qualitative research approach, this study gathers data through in-depth interviews with four university teachers and focus group discussion with five students of higher education based on purposive sampling. It delves into teachers’ and students’ lived experiences regarding assessment practices. The findings not only shed light on the multifaceted perceptions of grading systems and assessment strategies but also offer valuable insights into enhancing the fairness and quality of student evaluation. The implications of this study are significant, offering recommendations informed by practitioner enquiry to guide policymakers, academic leaders and educators in refining student assessment practices, ultimately enhancing learning outcomes and enriching educational experiences.